A formação de oficiais e as políticas educacionais da Academia da Força Aérea Brasileira. - Demo, Mauriceia Aparecida de Oliveira (2006)
Through this paper, the historic data about the Academia da Força Aérea is shown, from its transfer to Pirassununga until today. It emphasizes mainly a retaking of the curricular changings occured in this period, considering how and why these one happened. It describes, hereby, how the Administration Bussiness Course was set in this Academia, questioning their possible causes and consequences. The goal of this work is, mainly, to provoke a reflection about what should be the military profile in our society, what this society expects from their military people and how the Força Aérea Oficial s education should be so they can develop their main role.